Analisis implementasi akad murabahah pada produk pembiayaan cicil emas di Bank Syariah Indonesia KCP Selong Lombok Timur, Nusa Tenggara Barat - Hidayaturrahmaniah, Nadiya; Suriani (Management Journal and Economic Review, 2023)
This study aims to determine the implementation and constraints of murabahah contracts on gold installment financing products at BSI KCP Selong. The method used in this research is qualitative research with a descriptive approach. The primary research data comes from the BSI bank and customers of gold installment financing products. Data collection techniques were carried out using observation, interview, and documentation techniques. Data analysis was carried out using the inductive method by developing facts or facts that were obtained and could be developed from the results of the research conducted. The results of the study show that (1) The implementation of a murabaha contract occurs when the customer wants to buy gold from the bank in installments for a period agreed upon by the customer and the bank. BSI KCP Selong, in implementing this murabaha contract, uses a rahn system, or pawning system. Where in this product the customer guarantees in this installment, namely gold. So that the goods that the customer repays will be given after the customer has paid off the financing. (2) Obstacles in implementing gold installment financing occur during promotions and when gold prices rise. Therefore, BSI KCP Selong needs to do more promotion to market this gold installment product. In practice, this research is expected to help develop gold installment financing at Bank Syariah Indonesia KCP Selong by knowing what obstacles occur so that it is easier to find solutions to these obstacles.